Post-earthquake system identification of an 18-story RC building in Nepal - Yu, Hanshun. (2017)
Abstract: This thesis presents a study about assessing the performance of an 18-story RC building, damaged during the Gorkha Earthquake 2015, using post-earthquake vibration data. The building was instrumented with 15 accelerometers that measured its ambient acceleration response. A shaker test was carried out to get accurate calibration factors for the used sensors. Once the recorded data are calibrated and processed, the modal parameters of the test structure are identified using an operational modal analysis (output-only) method. Moreover, a linear elastic finite element model of the building is developed to estimate the dynamic properties of the test structure. The identified model parameters are compared to those of the model. It is observed that the first two vibration modes of the model can be accurately correlated with the system identification results, validating the model.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Civil Engineering.; Advisor: Babak Moaveni.; Committee: Masoud Sanayei, Andre Barbosa, and Andreas Stavridis.; Keyword: Civil engineering.